Was heißt Nachfolge Jesu heute? - Zachhuber, J (2015)
The unpublished seminar paper seeks an interpretation of Bonhoeffer's thought on the basis of the assumption that for him Christian theory and praxis formed a unity. It therefore takes as its starting point his book Discipleship (Nachfolge) and argues that 'Nachfolge' is a very helpful concept to grasp the unity of Bonhoeffer's life and thought.